Thermal Inactivation of African Swine Fever Virus in Swill - Nuanualsuwan, Suphachai; Songkasupa, Tapanut; Boonpornprasert, Prakit; Suwankitwat, Nutthakarn; Lohlamoh, Walaiporn; Nuengjamnong, Chackrit (Frontiers in Veterinary Science, 2022)
The indirect transmission of the African swine fever virus (ASFV) is through contaminated fomite, feed ingredients, pork and pig-derived products including swill, as ASFV is highly stable within suitable organic material. Some previous studies indicated that ASFV outbreaks were associated with swill feeding, particularly in smallholder pig farms. These outbreaks emphasize the significance of the appropriate heat treatment of swill to eliminate ASFV residual titer. The World Organisation for Animal Health (OIE) recommended the heat treatment of swill at a temperature of at least 90 °C for at least 60 min with continuous stirring while the Food and Agriculture Organization (FAO) recommended heat treatment at 70 °C for 30 min. The lack of scientific evidence regarding ASFV inactivation by heat treatment of swill leads to such inconsistent recommendations. Therefore, the objectives of this study were to assess the thermal inactivation of ASFV in three swill formulae and to develop a DT model to predict DT at some other inactivation temperatures. The significant reduction of ASFV in swill occurred at temperatures as low as 60 °C. DT or decimal reduction time (DRT) is defined as the time required to reduce the virus titer by 1 log and this was also used as a comparative index of heat resistance. The mean D60, D70, D75, and D80 of ASFV in three swill formulae were in the ranges 23.21–33.47, 5.83–10.91, 2.15–2.22, and 1.36–1.47 min, respectively. These DT could be widely used for any nutritive composition of swill other than the three swill formulae in this study since there was no statistical difference of all DT of ASFV across three swill formulae. Based on D70 and the predicted D90 from the DT model in this study including the highest ASFV titer in pork products, the calculated inactivation times at 70 and 90 °C were 119 and 4 min, respectively.